2006
DOI: 10.1158/1055-9965.epi-05-0653
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms in Base-Excision Repair Pathway Genes and Risk of Breast Cancer

Abstract: Impaired base-excision repair (BER) function can give rise to the accumulation of DNA damage and initiation of cancer. We evaluated whether genetic variation in six BER pathway genes (XRCC1, ADPRT, APEX1, OGG1, LIG3, and MUTYH) is associated with breast cancer risk in two large population-based case-control studies in the United States (3,368 cases and 2,880 controls) and Poland (1,995 cases and 2,296 controls). A detailed evaluation was first done in a subset of 1,898 cases and 1,514 controls with mouthwash D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
96
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(110 citation statements)
references
References 21 publications
12
96
2
Order By: Relevance
“…APE1 Asp148Glu variants are the most common APE1 polymorphisms identified in the general population that result in a single amino acid substitution (Hung et al, 2005). Zhang et al (2006) found no association between the APE1 Asp148Glu variant and breast cancer risk among non-Hispanic white Americans, whereas Suleeporn et al (2008) reported a significant protective effect of the APE1 148Glu allele in Thai women. Subsequently, a meta-analysis of the APE1 Asp148Glu polymorphism , which included 5 studies with a total of 2,539 breast cancer patients and 2,572 control subjects, showed no obvious association between APE1 148Glu and breast cancer (Wu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…APE1 Asp148Glu variants are the most common APE1 polymorphisms identified in the general population that result in a single amino acid substitution (Hung et al, 2005). Zhang et al (2006) found no association between the APE1 Asp148Glu variant and breast cancer risk among non-Hispanic white Americans, whereas Suleeporn et al (2008) reported a significant protective effect of the APE1 148Glu allele in Thai women. Subsequently, a meta-analysis of the APE1 Asp148Glu polymorphism , which included 5 studies with a total of 2,539 breast cancer patients and 2,572 control subjects, showed no obvious association between APE1 148Glu and breast cancer (Wu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Base excision repair (BER) is a highly conserved essential mechanism for maintaining genome integrity. Impaired BER function can give rise to the accumulation of 8-OHG lesion and other DNA base lesions, which may influence the initiation and progression of cancer (28). OGG1 is a key enzyme in short-patch BER because it recognises and performs initial excision of the most common form of oxidative DNA base damage, 8-OHG (29).…”
Section: Discussionmentioning
confidence: 99%
“…7 It is known that mutations in mismatch-repair genes increase susceptibility to cancer in organs other than the colon, but former data published regarding a possible association between MutYH mutations and breast cancer risk are conflicting. [8][9][10][11][12][13][14] We studied the prevalence of the 2 commonly described founder mutations in MutYH, a glycine-to-aspartic acid substitution at codon 396 (G396D) and a tyrosine-to-cysteine substitution at codon 179 (Y179C), in a case-control study of breast cancer that was restricted to Sephardi Jews in whom we noted a high prevalence of these mutations (unpublished results).…”
Section: Introductionmentioning
confidence: 99%